The eyes of Gray Wolf - London, Jonathan, 1947-; Van Zyle, Jon (San Francisco : Chronicle Books, 1993)
On a cold Northern night, a restless gray wolf encounters an unknown wolf pack, from which a young white wolf steps out and they become mates.
School Library Journal.
Booklist starred.
Publisher's Weekly.
4.1
K-3
Keywords: Wolves -- Fiction; Wolves -- Fiction; Wolves -- Fiction